Pemilihan Supplier Bahan Baku Bangunan Dengan Metode Analytical Hierarchy Process (AHP) Pada PT. Cipta Nuansa Prima Tangerang - Rani Irma Handayani; Yuni Darmianti (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2017)
Supplier is one of the most important parts of a construction services provider company. PT. Nuance Prima Cipta Tangerang is a contracting company that offers construction services. Since the number of suppliers, PT. Nuance Prima Cipta Tangerang difficulty in choosing suppliers with their respective advantages. Therefore, use AHP (Analytical Hierarchy Process) for supplier selection process to make it more objective. Broadly speaking, AHP (Analytical Hierarchy Process) is the process of comparing criteria into alternatives, the greater the value is generated, then the main well to the supplier selected. By using the AHP method obtained the final value for each akternatif Lead A 39%, 12% and Supplier B Supplier C 49%